2013
DOI: 10.1002/emmm.201201864
|View full text |Cite
|
Sign up to set email alerts
|

Usp18 deficient mammary epithelial cells create an antitumour environment driven by hypersensitivity to IFN‐λ and elevated secretion of Cxcl10

Abstract: The theory of cancer immunoediting refers to mechanisms by which the immune system can suppress or promote tumour progression. A major challenge for the development of novel cancer immunotherapies is to find ways to exploit the immune system's antitumour activity while concomitantly reducing its protumour activity. Using the PyVmT model of mammary tumourigenesis, we show that lack of the Usp18 gene significantly inhibits tumour growth by creating a tumour-suppressive microenvironment. Generation of this antitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 54 publications
2
56
0
Order By: Relevance
“…The potential for IFN-λ's influence on the balance between Th1 and Th2 immune responses to impact cancer was recently highlighted by an investigation of the IFN-inducible gene USP18 in a mouse model of spontaneous breast cancer by Burkart et al [43]. USP18 is known to be a negative regulator of type I IFN responses, and USP18 deficiency has been reported to have an inhibitory effect on the development of leukemia.…”
Section: Immune Modulatory Effects Of Ifn-λmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for IFN-λ's influence on the balance between Th1 and Th2 immune responses to impact cancer was recently highlighted by an investigation of the IFN-inducible gene USP18 in a mouse model of spontaneous breast cancer by Burkart et al [43]. USP18 is known to be a negative regulator of type I IFN responses, and USP18 deficiency has been reported to have an inhibitory effect on the development of leukemia.…”
Section: Immune Modulatory Effects Of Ifn-λmentioning
confidence: 99%
“…To investigate this, Burkart et al [43] analyzed the expression of T cell-specific chemokines and found that the Cxcr3 ligands Cxcl10 and Cxcl11 were significantly upregulated in PyVmT/USP18 KO tumors. Since expression of Cxcr3 is associated with Th1 cells, the authors investigated if PyVmT/USP18 KO tumors showed a Th1 cytokine profile and found they had increased expression of IFN-γ and decreased expression of the Th2 cytokines IL-4 and IL-13.…”
Section: Immune Modulatory Effects Of Ifn-λmentioning
confidence: 99%
“…The authors reported a role for NK cells, T cells and neutrophils in mediating the antitumor activity of IFN-λ. We and other groups have also validated the antitumor role of IFN-λ in other tumor models, including lung [77], hepatoma [78], esophagus [79,80], breast c ancer [81], prostate [82] and colon cancer [83].…”
Section: Development Of Ifn-λ As Antitumor Agent: Preclinical Datamentioning
confidence: 73%
“…Durable antitumor immune responses have also been reported for IFN-λ [78]. These responses have largely been associated with induction of T-cell responses, as reported in the antitumor activity of IFN-λ in melanoma [75], fibrosarcoma [76], lung adenocarcinoma [79] and breast cancer [81]. However IFN-λ-induced innate immunity, largely represented by NK-cell induction, was demonstrated in numerous cancer models, including melanoma [75], fibrosarcoma [76], hepatoma [78], lung adenocarcinoma [79] and prostate adenocarcinoma [82].…”
Section: Development Of Ifn-λ As Antitumor Agent: Preclinical Datamentioning
confidence: 93%
See 1 more Smart Citation